Cooperativity in O2 binding to iron porphyrins. - Collman, J P (1978)
The solid-gas O2 binding equilibrium has been studied for for ferrous "picket fence" porphyrinates with sterically hindered axial imidazoles. Such systems show significant cooperativity in their binding of O2: at low O2 pressures a low O2 affinity form exists, and at high O2 pressures a higher O2 affinity form develops. Direct analogies are drawn to the cooperativity shown in O2 binding by hemoglobin. These model systems mimic hemoglobin quantitatively.